2019
DOI: 10.3390/rs12010062
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the Big Earth Observation Data via Cloud Computing and DGGS: Opportunities and Challenges

Abstract: In the era of big data, the explosive growth of Earth observation data and the rapid advancement in cloud computing technology make the global-oriented spatiotemporal data simulation possible. These dual developments also provide advantageous conditions for discrete global grid systems (DGGS). DGGS are designed to portray real-world phenomena by providing a spatiotemporal unified framework on a standard discrete geospatial data structure and theoretical support to address the challenges from big data storage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 78 publications
(116 reference statements)
0
40
0
1
Order By: Relevance
“…Finally, the reliability of this method is verified by case study [14]. Ahmadzadeh et al (2019) evaluated the performance of earthquake stress command headquarters in Alborz Medical Sciences University in earthquake accident and disaster risk management, and found that the command headquarters responded timely and could make effective decisions [15]. At present, there are many researches on the earthquake emergency system, but most of them focus on the disaster management after the earthquake.…”
Section: A Earthquake Emergency Command Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, the reliability of this method is verified by case study [14]. Ahmadzadeh et al (2019) evaluated the performance of earthquake stress command headquarters in Alborz Medical Sciences University in earthquake accident and disaster risk management, and found that the command headquarters responded timely and could make effective decisions [15]. At present, there are many researches on the earthquake emergency system, but most of them focus on the disaster management after the earthquake.…”
Section: A Earthquake Emergency Command Researchmentioning
confidence: 97%
“…Cloud computing is a distributed computing method, which mainly refers to the process of computing and decomposing massive data into numerous small programs through the network "cloud", and then the system composed of multiple servers will analyze and process these small programs, and finally return the processing results to users [16,17]. Cloud computing is also being used to build emergency systems, d 'Oro et al (2019) built a novel architecture based on cloud computing and Internet of things technology to solve the problems of response capacity, bandwidth demand, privacy, and availability in emergency systems.…”
Section: B Research Status Of Cloud Computing Technologymentioning
confidence: 99%
“…However, many applications generate their data in space, e.g., Earth imagery, weather observations, and remote sensing. Data analytics on "Big Earth Observation Data" [12,13,35,55] is seen as a lucrative and expanding market [41], so much so, that Amazon recently launched its "AWS Ground Station" service targeting this segment. At least one of the LEO networks planned, Starlink, has hinted that its satellites may additionally produce such sensing data [40].…”
Section: Processing Space-native Datamentioning
confidence: 99%
“…The integer index is assigned to each cell for location representation. Based on these characteristics, DGGSs have aroused widespread academic attention and been developed in various fields, such as global gazetteer [5], ocean tidal simulation [6], and handling big Earth data with cloud computing technology [7]. The Open Geospatial Consortium (OGC) has released an abstract specification for DGGS [8], which highlights equal-area cells desirable in the integrated analysis of…”
Section: Introductionmentioning
confidence: 99%